Effects of leader-member exchange on employee motivation: a case study in Malaysia and UK - Selvakumaran, Arokiasamy (2014)
This project deals with a case study in an engineering department in Tasco Electronic M’sia Sdn. Bhd., (pseudonym) where the department were poorly performing, employees are engaged in low motivation and increased resignation rate within the department, as a result of poor employee-manager relationship (Leader-Member Exchange, LMX). This cross-sectional research study was conducted in Tasco Electronic M’sia Sdn. Bhd, located in Chukai, Terengganu and in their sister company, located in Newcastle, United Kingdom. The objective of this study is to examine to what extent LMX has an effect on employee motivation and also to determine if there are any difference in the effect of LMX on motivation in a high social power distance region (Malaysia) compared in a low social power distance region (United Kingdom). The instrument that is been used in this study is questionnaire and the questionnaire of this study consist of three (3) reputable scales which tapped on LMX, Social Power Distance and Employee’s Work Motivation. Through these scales, level of LMX, level of employee-manager social distance and employee’s work motivation among the respondents were determined. Samples were picked conveniently making the sampling to be a non-probability sampling. Responses from the respondents were collected via online survey, SoGoSurvey and SPSS was used to perform the analysis. Independent samples t-test was conducted to investigate the difference between both companies and through three (3) level hierarchical moderation regression analyses, hypotheses were tested. It is shown that Tasco Electronic M’sia Sdn. Bhd., has higher manager-employee social gap (social power distance), weaker relationship between leader and employee (LMX), higher amotivation, higher controlled motivation and similar level of autonomous motivation in comparison to their sister company in United Kingdom. It can also be concluded that both the companies experience the similar effects of LMX on employee’s motivation as social power distance was not found to moderate the relationship between LMX and employee motivation.